Born from pre-eclamptic pregnancies predisposes infants to altered cortisol metabolism in the first postnatal year - Broughton Pipkin, Fiona; Mistry, Hiten D.; Roy, Chandrima; Dick, Bernhard; Waugh, Jason; Chikhi, Rebecca; Kurlak, L.O.; Mohaupt, Markus (BioScientifica, 2015)
Pre-eclampsia leads to disturbed fetal organ development, including metabolic syndrome, attributed to altered pituitary-adrenal feedback loop. We measured cortisol metabolites in infants born from pre-eclamptic and normotensive women and hypothesised that glucocorticoid exposure would be exaggerated in the former. Twenty-four hour urine was collected from infants at months 3 and 12. Cortisol metabolites and apparent enzyme activities were analysed by gas chromatography-mass spectrometry. From 3 to 12 months, excretion of THS, THF and pregnandiol had risen in both groups; THF also rose in the pre-eclamptic group. No difference was observed with respect to timing of the visit or to hypertensive status for THE or total F metabolites (P>0.05). All apparent enzymes activities, except 17α-hydroxylase, were lower in infants at 12 compared to 3 months in the normotensive group. In the pre-eclamptic group, only 11β-HSD activities were lower at 12 months.17α-hydroxylase and 11β-HSD activities of tetrahydro metabolites were higher in the pre-eclamptic group at 3 months (P<0.05). 11β-hydroxylase activity increased in the pre-eclamptic group at 12 months. Cortisol excretion, determined by increased 11β-hydroxylase, compensates for high 11β-HSD-dependent cortisol degradation at 3 months and at 12 months counterbalances the reduced cortisol substrate availability in infants born from pre-eclamptic mothers.